The Relationship Of Single Parent Parenting On Children's Intelligence - sudirman, sulaeman (Sahabat Publikasi Kuu, 2024)
Single parents are parents consisting of a father and mother who are ready to carry out their duties with full responsibility as a single parent. Parenting styles play a very important role in determining a child's level of intelligence because every parent wants intelligent children, for example by getting high grades for their lessons at school. The aim of this research is to analyze the relationship between single parent parenting and children's intelligence in Sidrap Regency. This research method is quantitative with a cross sectional approach. This research was carried out in 2 areas, namely at SD Negeri 14 and SD Negeri 17 Sidrap Regency in September-October 2023. The sampling technique used in this research was purposive sampling using the Chi-square test. The results of research on democratic single parent parenting showed good child intelligence (40.0%). Based on the chi-square test, a p-value of 0.029 <0.05 was obtained. From these results it can be concluded that there is a relationship between single parent parenting and children's intelligence in Sidrap Regency.